Willingness to Pay for Environmental Goods in East Malaysia - Audrey, Liwan; Dezriana, Victer; Corrado, Riccardo; Nur Zaimah, Ubaidillah; Yau, Josephine Tan Hwang; Rosita, Hamdan (Knowledge Words Publications, 2020)
This research has been conducted to investigate consumers’ willingness to pay for environmental goods in East Malaysia, and specifically in Sabah and Sarawak. The data were collected from 250 respondents. The respondents’ environmental awareness has been linked to their perceived behavioural control and willingness to pay for environmental goods. The key findings of this study indicate that attitude, and perceived behavioural have positive influence on the willingness to pay for environmental goods. It is anticipated that the findings of this research should lead to the introduction of widespread awareness programmes that highlight the benefits and the implications of green product towards environment. To encourage the consumption of environmental goods its recommended to introduce environmental education at an early age. In addition, social media also stands out as the best platform to reach the heaviest green consumers.